(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Trastuzumab is recombinant humanized monoclonal IgG antibody used in the treatment of metastatic breast cancer. It blocks the overexpression of tyrosine kinase Her 2 family receptors and downregulation of pathways. Genetic optimizations like gene optimization and expression vector optimization are the key elements to enhance monoclonal antibody expression. Expression vector optimization includes major parameters like selection of right promoters, poly A tail selection of genome integrating elements. Codon optimization is gene designing approach without affecting the amino acid sequence of the protein. Current research work involves development of codon optimization algorithm for trastuzumab heavy and light chain gene and comparative analysis of expression in different vectors.